PENGARUH MASUKAN PERSONIL DAN KEPEMIMPINAN TERHADAP PELAYANAN PUBLIK MELALUI KETERLIBATAM PERSONIL PADA DIREKTORAT LALU LINTAS POLDA SULAWESI SELATAN - Bahrul S; Moh Hatta; Muh Ashary Anshar; Muhammad Nasir (Program Pasca Sarjana IBK Nitro, 2023)
The formulation of the problem in this study is Does Masukan personilaffect the Pelayanan publik at the Traffic Directorate of the South Sulawesi Regional Police? Does Masukan personilaffect Keterlibatan personil at the South Sulawesi Regional Police Traffic Directorate? Does Leadership affect the Pelayanan publik at the Traffic Directorate of the South Sulawesi Regional Police? Does Leadership affect Keterlibatan personil at the South Sulawesi Regional Police Traffic Directorate? Does Masukan personilaffect Pelayanan publik through Keterlibatan personil at the Traffic Directorate of the South Sulawesi Police? This research was conducted at the South Sulawesi Regional Police. The sampling technique used Accidental Sampling to 76 respondents from the South Sulawesi Regional Police Traffic Directorate. The reason for determining the object of this research is because it is easily accessible by researchers so that it can facilitate the implementation of research. From the results of the study it can be concluded that the Employee Voicefactor has a positive and significant effect on personil Keterlibatan personil at Traffic Police of South Sulawesi Regional Police. The Leadership has a positive and significant effect on Personil Keterlibatan personil at the Traffic Police of South Sulawesi Regional Police. The Masukan personilhas a negative and insignificant effect on the Pelayanan publik for trafficked personnel at the South Sulawesi Regional Police. The leadership factor has a positive and significant effect on the personil Pelayanan publik in the Traffic Police of South Sulawesi Regional Police. The Keterlibatan personil has a positive and significant effect on personil Pelayanan publik at the South Sulawesi Regional Police Traffic Unit.